2003
DOI: 10.1164/rccm.200212-1397oc
|View full text |Cite
|
Sign up to set email alerts
|

Snoring, Intermittent Hypoxia and Academic Performance in Primary School Children

Abstract: Sleep-disordered breathing is associated with impaired attention and neurocognitive deficits. We assessed the association of snoring and intermittent hypoxia with poor academic performance in third grade school children (1,144 children). Snoring frequency and intermittent hypoxia were investigated using parental questionnaire and nocturnal home pulse oximetry. Intermittent hypoxia was specified as desaturation events of 90% or less pulse oximeter saturation. Poor academic performance was defined as grade 4-6 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
146
2
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(172 citation statements)
references
References 32 publications
13
146
2
11
Order By: Relevance
“…Comparisons with the target population (n54,109) revealed good to excellent representativeness of the study sample concerning sex distribution, socioeconomic status, academic performance and doctor-diagnosed asthma [19]. Children were screened twice using a widely used and partially validated parental SDB-questionnaire (SDB-Q) [20][21][22][23][24] and nocturnal home pulse oximetry (HPO) [25][26][27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons with the target population (n54,109) revealed good to excellent representativeness of the study sample concerning sex distribution, socioeconomic status, academic performance and doctor-diagnosed asthma [19]. Children were screened twice using a widely used and partially validated parental SDB-questionnaire (SDB-Q) [20][21][22][23][24] and nocturnal home pulse oximetry (HPO) [25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…Limitations Limitations of the current study have been discussed elsewhere [19,24]. Briefly, there might be a selection bias if subjects with symptoms were more likely to agree to participate.…”
Section: Sleep-related Disorders Ms Urschitz Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…The aetiological causes, risk factors and course of sleep and behavioral disturbances in childhood are complex [4][5][6][7][8][9][10][11][12][13][14]. Moreover, prevalence of psychiatric behavioral disturbance increases up to 17% and 26% in school age [15].…”
Section: Introductionmentioning
confidence: 99%
“…OSA is associated with daytime sleepiness, poor academic performance, stroke, hypertension and ischemic heart disease (3,4).Furthermore, not only habitual snoring combined with OSA or upper airway resistance syndrome, but also habitual snoring alone appears to be linked with impaired daytime functioning in adults (5,6). Population based cohort studies revealed age, obesity, smoking, nasal (eg, septal deviation, rhinitis) and pharyngeal (eg, hypertrophy of tonsils, otitis) problems as independent risk factors for self reported habitual snoring (7,8).Professional wrestlers have some of risk factors for snoring including male gender, high body mass index (BMI) and large neck circumference.…”
Section: Introductionmentioning
confidence: 99%